Pseudomonas fluorescens: A Bioaugmentation Strategy for Oil-Contaminated and Nutrient-Poor Soil - Gutiérrez, Eduardo Jahir (Int J Environ Res Public Health, 2020)
Bioremediation technology is one of the most profitable and sustainable strategies for remediating soils contaminated with hydrocarbons. This study focuses on assessing the influence of biostimulation and bioaugmentation with Pseudomonas fluorescens to contribute to the removal of total petroleum hydrocarbons (TPHs) of a soil. Laboratory studies were carried out (measurements of emitted CO(2), surface tension, and residual TPH) to select the best bioaugmentation and biostimulation treatment. The sources of C, N, and P were glucose–yeast extract, NH(4)Cl–NaNO(3), and K(2)HPO(4)–K(3)PO(4), respectively. The effect of culture conditions on the reduction of TPH and respiratory activity was evaluated through a factorial design, 2(3), in a solid culture system. After 80 days of incubation, it was observed that treatments of yeast extract–NH(4)Cl–K(2)HPO(4) (Y4) and glucose–NaNO(3)–K(3)PO(4) (Y5) presented a higher level of TPH removal (20.91% and 20.00% degradation of TPH, respectively). Biostimulation favors the production of biosurfactants, indirectly measured by the change in surface tension in the soil extracts. The treatments Y4 and Y5 showed a lower change value of the surface tension (23.15 and 23.30 mN·m(−1) at 25 °C). A positive correlation was determined between the change in surface tension and the removal of TPH; hence there was a contribution of the biosurfactants produced to the removal of hydrocarbons.